FRUIT PEEL EXTRACT OF Sygyzium cumini AS AN ALTERNATIVE STAINING FOR PERIPHERAL BLOOD SMEAR PREPARATIONS - Ayu Nirmala Sari; Rizky Ardila; Zahara Afnita (Prosiding Seminar Nasional Biotik, 2022)
Peripheral Blood Smear is preparations of human blood cells made by smear method and through a staining process in hematological examination to see the elements of peripheral blood cells, namely erythrocytes, leukocytes and platelets. The result of the Peripheral Blood Smear examination is the quality of the staining. This study was conducted with the aim of observing blood cells in blood smear preparations using aqueous extract from the skin of the jamblang fruit (Sygyzium cumini) as an alternative dye to replace Giemsa dye. This research was conducted by comparing the results of erythrocytes, leukocytes and platelets with Giemsa staining and using an alternative staining of fruit peel extract. The sample in this study used blood, and then it was made as a thin blood smear. The results of this study showed that only erythrocytes had a slightly good staining quality while platelets and leukocytes were not good because the acid content in Sygyzium cumini extract could not bind the cell nucleus in platelets and leukocytes. The morphology of normal erythrocyte cells obtained was round and oval disc-like (biconcave) with a purple center and pale edges.